CHOICE OF OPTIMA! PARAMETERS OF TECHNOLOGY OF THE TUBE SLUGS IN CIRCULAR FURNACE - V. I. Timoshpoiski; M. L. German; S. M. Kabishov; S. V. Korneev (Литьë и металлургия)
The analysis of the tube shells heating technology in annular furnaces is carried out, the main technological factors, exerting the most influence on energotechnological indices of the process and quality of heating, are determined.